The Long-Term Fiscal Impact of Immigrants in the Netherlands, Differentiated by Motive, Source Region and Generation - Jan van de Beek; Joop Hartog; Gerrit Kreffer; Hans Roodenburg (Institute of Labor Economics (IZA), 2024)
We use very detailed microdata on fiscal contributions and benefits of the entire population to calculate the discounted lifetime net contribution of the immigrant population present in The Netherlands in 2016. We differentiate by immigration motive and up to 87 source regions. Labour migrants' net contribution is positive, study, family and asylum immigrants' contributions are negative. Second generation scholastic performance scores at age 12 by social background are similar to scores for native Dutch children, highest education attained for given test scores is also similar, but incomes for given education levels are lower, and so are net contributions. The gap between net contributions of individuals with immigrant background and without immigrant background does not root in attained levels of schooling but in the benefits from schooling. Regional cultural distance to Protestant Europe is associated with large fiscal net contributions.
Keywords: H5; J6; J15; 330; fiscal incidence; immigrants; cultural distance